1999
DOI: 10.1128/mcb.19.11.7759
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Dbl and Dbs Transformation on MEK and NF-κB Activation

Abstract: Dbs was identified initially as a transforming protein and is a member of the Dbl family of proteins (>20 mammalian members). Here we show that Dbs, like its rat homolog Ost and the closely related Dbl, exhibited guanine nucleotide exchange activity for the Rho family members RhoA and Cdc42, but not Rac1, in vitro. Dbs transforming activity was blocked by specific inhibitors of RhoA and Cdc42 function, demonstrating the importance of these small GTPases in Dbs-mediated growth deregulation. Although Dbs transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 69 publications
(141 reference statements)
6
109
2
Order By: Relevance
“…Indeed, a number of studies have reported crosstalk between the RhoA signalling pathway and NF-kB (Perona et al, 1997;Montaner et al, 1998Montaner et al, , 1999Hippenstiel et al, 2002). In addition, members of the transforming protein family Dbl of Rho GEFs efficiently activate transcription from NF-kB-responsive elements (Whitehead et al, 1999), but the molecular basis for this activation remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of studies have reported crosstalk between the RhoA signalling pathway and NF-kB (Perona et al, 1997;Montaner et al, 1998Montaner et al, , 1999Hippenstiel et al, 2002). In addition, members of the transforming protein family Dbl of Rho GEFs efficiently activate transcription from NF-kB-responsive elements (Whitehead et al, 1999), but the molecular basis for this activation remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…IκB(SS) is a derivative of IκBκ that is mutated on serines 32 and 36 [30]. Since this mutant cannot be phosphorylated by the IKK complex, it binds irreversibly to NF-κB and blocks nuclear translocation.…”
Section: Rhob Activates Nf-κb Through the Non-classical Pathwaymentioning
confidence: 99%
“…Which RhoA-modulated transcription factors are involved in this process is unknown, but the presence of AP-1-and NF-B-responsive elements in the uPAR promoter points to a role of both TFs in this process (Dang et al, 1999;Wang et al, 2000). Furthermore, NF-B has also been related to Rho GTPase-induced neoplastic transformation (Whitehead et al, 1999). Recently, Marinissen et al (2001) described the role of two other transcription factors, ATF2 and MEF2A, in RhoA-mediated transformation via transcription of the c-jun gene.…”
Section: Introductionmentioning
confidence: 99%